Chloride concentration affects soil microbial community - Gryndler, Milan; Rohlenová, Jana; Kopecký, Jan; Matucha, Miroslav (Chemosphere, 2008)
We studied the effect of increased inorganic chloride concentration on forest soil microflora in a laboratory experiment. Microbial DNA extracted from experimental soil samples was amplified with PCR using primer pairs specifically amplifying bacterial, eukaryotic and fungal DNA fragments. The resulting amplified DNA was further used for terminal restriction fragment length polymorphism (TRFLP) analysis. Our work revealed that chloride concentration affects the indigenous microbial community in experimental soil. This was documented on an unidentified microorganism whose DNA was detectable in soil high in chloride but was not found in soil with low chloride concentration. The presence of the organism responsive to increased chloride concentration was associated with the highest observed value of chlorination of humic acid, suggesting possible role of this organism in soil chlorine turnover. High chloride concentration in the soil tended to decrease the rate of degradation of trichloroacetic acid. The problems connected with measurement of chlorination rates in soil are discussed.
Keywords: DNA fungální; DNA, Fungal; DNA bakterií; Polymorphism, Restriction Fragment Length; Carbon Radioisotopes; Chlorides; chloridy; Soil Pollutants; látky znečišťující půdu; půda; Colony Count, Microbial; DNA, Bacterial; Carbon Dioxide; radioizotopy uhlíku; půdní mikrobiologie; počet mikrobiálních kolonií; oxid uhličitý; Soil; polymorfismus délky restrikčních fragmentů; Soil Microbiology